Cultural anthropology - Nanda, Serena (Wadsworth/Thomson Learning, 2007)
Part I. INTRODUCTION TO CULTURAL ANTHROPOLOGY. 1. Anthropology and Human Diversity. 2. Human Evolution. 3. Doing Cultural Anthropology. 4. The Idea of Culture. 5. Language. Part II. FAMILIES IN SOCIETY. 6. Making a Living. 7. Economics. 8. Marriage, Family, and Domestic Groups. 9. Kinship. Part III. EQUALITIES AND INEQUALITIES. 10. Gender. 11. Political Organization. 12. Stratification: Class and Caste. 13. Stratification: "Race" and Ethnicity. Part IV. SYMBOLS AND MEANINGS. 14. Religion. 15. Creative Expression: Anthropology and the Arts. Part V. CULTURE CHANGE. 16. Culture Change and the Modern World. Appendix: A Brief Historical Guide to Anthropological Theory